Immune biomarkers of treatment failure for a patient on a phase I clinical trial of pembrolizumab plus radiotherapy. Issue 1 (December 2016) - Alexander, Gregory; Palmer, Joshua; Tuluc, Madalina; Lin, Jianqing; Dicker, Adam; Bar-Ad, Voichita; Harshyne, Larry; Louie, Jennifer; Shaw, Colette; Hooper, D.; Lu, Bo
Abstract Background Pembrolizumab is a monoclonal antibody that is designed against programmed cell death protein 1 (PD-1). Pembrolizumab and other immunocheckpoint-blocking monoclonal antibodies work by modulating a patient's own immune system to increase anti-tumor activity. While immunocheckpoint blockade has shown promising results, only 20–40 % of patients experience objective clinical benefit. Differences in individual tumor biology and the presence multiple immune checkpoints present a challenge for treatment. Because radiotherapy has immunomodulatory effects on the tumor microenvironment, it has the potential to synergize with immunotherapy and augment tumor response. NCT02318771 is a phase 1 clinical trial designed to investigate the immunomodulatory effects of radiation therapy in combination with pembrolizumab. Case presentation The patient is a 64-year-old male with metastatic clear cell renal cell carcinoma, Fuhrman grade 4, pathologically staged as T3 N0. Metastatic disease was well controlled for several years with sunitinib. Following disease progression, he was switched to axitinib. When disease progression continued, the patient was enrolled in NCT02318771, a phase 1 clinical trial combining radiotherapy and pembrolizumab. The patient experienced unusually rapid disease progression during treatment, which was confirmed by repeated CT scans to rule out pseudoprogression. Tissue biopsies and peripheral blood draws were obtained before, during, and after treatment. Samples were analyzed to provide plausible rationale for rapid treatment failure. Conclusions Biomarker analysis demonstrated an absence of TILs, which may be a cause of treatment failure as pembrolizumab works through T cell-dependent mechanisms. Furthermore, the presence of other non-redundant immune checkpoints in the periphery and tumor microenvironment presents a treatment challenge. Additionally, the radiation dose and fractionation schedule may have played a role in treatment failure as these factors play a role in the effect radiotherapy on the tumor microenvironment as well as the potential for synergy with immunotherapy. Trial registration An Exploratory Study to Investigate the Immunomodulatory Activity of Radiation Therapy (RT) in Combination With MK-3475 in Patients With Recurrent/Metastatic Head and Neck, Renal Cell Cancer, Melanoma and Lung Cancer, NCT02318771 .